Amplification of whole mRNA in A549 adenocarcinoma cell by template-switching method / Muhammad Ariff Mohamad Hamil - Mohamad Hamil, Muhammad Ariff (2015)
Polymerase Chain Reaction (PCR) is a DNA amplifying technique pioneered by Kary Mullis at Cetus Corporation in the early 1980's (Handyside et al., 1989) PCR is a technique amplifying a specific DNA component from very small quantities of DNA source component and also from the source with poor quality into numerous of copies. It involve series of steps that is denaturation, annealing and primer extension. For the first steps is denaturation process, the DNA is heated to 95°C to unwind the helical structure into single stranded DNA. Next step is the annealing process where complementary strand are hybridized with primers. The temperature used during this step depended on the primer size and its homology to the target DNA.